Calcule a e b. Sabendo que 1 é raiz de P(x) = ax3 - 2x² + bx - 1 e que P(2)= 3
Soluções para a tarefa
Respondido por
7
P(x) = ax³ - 2x² + bx - 1
P(2) = 3
a(2)³ - 2(2)² + b(2) - 1 = 3
8a - 8 + 2b - 1 = 3
8a + 2b = 3 + 1 + 8
8a + 2b = 12
4a + b = 6
P(1) = 0
ax³ -2x² + bx - 1 = 0
a(1)³ - 2(1)² + b(1) - 1 = 0
a - 2 + b - 1 = 0
a + b = 3
![\left \{ {{a + b=3} \atop {4a + b=6}} \right. \\ \\ 3a = 3 \\ \\ a = 1 \\ \\ \\ a + b = 3
\\ 1 + b = 3 \\ b = 2 \left \{ {{a + b=3} \atop {4a + b=6}} \right. \\ \\ 3a = 3 \\ \\ a = 1 \\ \\ \\ a + b = 3
\\ 1 + b = 3 \\ b = 2](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Ba+%2B+b%3D3%7D+%5Catop+%7B4a+%2B+b%3D6%7D%7D+%5Cright.++%5C%5C++%5C%5C+3a+%3D+3+%5C%5C++%5C%5C+a+%3D+1+%5C%5C++%5C%5C++%5C%5C+a+%2B+b+%3D+3%0A+%5C%5C+1+%2B+b+%3D+3+%5C%5C+b+%3D+2)
P(x) = x³ - 2x² + 2x - 1
P(2) = 3
a(2)³ - 2(2)² + b(2) - 1 = 3
8a - 8 + 2b - 1 = 3
8a + 2b = 3 + 1 + 8
8a + 2b = 12
4a + b = 6
P(1) = 0
ax³ -2x² + bx - 1 = 0
a(1)³ - 2(1)² + b(1) - 1 = 0
a - 2 + b - 1 = 0
a + b = 3
P(x) = x³ - 2x² + 2x - 1
Perguntas interessantes
Filosofia,
11 meses atrás
Inglês,
11 meses atrás
Física,
11 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás